PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMK NEGERI 1 SURABAYA - Okta Rahmalina, Sari; Gofar, Abdul (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
achieving the goal of quality education. However, in practice, teacher performance often faces various challenges that can impact the effectiveness of the learning process. Therefore, it is important to understand the factors that can influence teacher performance, such as leadership, motivation, and organizational commitment. This study aims to determine whether leadership, motivation, and organizational commitment influence teacher performance. This study used a quantitative approach with a causal associative research approach. A population of 100 respondents served as the independent variable. Data collection techniques included observation, interviews, and questionnaires. Multiple linear regression was used for data analysis. The results showed that leadership significantly influenced teacher performance, motivation did not significantly influence teacher performance, while organizational commitment also significantly influenced teacher performance. Overall, leadership, motivation, and teacher commitment significantly influenced teacher performance at SMK Negeri 1 Surabaya, as evidenced by the calculated F-value > F-table.